HiC-Pro: an optimized and flexible pipeline for Hi-C data processing. Issue 1 (December 2015) - Servant, Nicolas; Varoquaux, Nelle; Lajoie, Bryan; Viara, Eric; Chen, Chong-Jian; Vert, Jean-Philippe; Heard, Edith; Dekker, Job; Barillot, Emmanuel
Abstract HiC-Pro is an optimized and flexible pipeline for processing Hi-C data from raw reads to normalized contact maps. HiC-Pro maps reads, detects valid ligation products, performs quality controls and generates intra- and inter-chromosomal contact maps. It includes a fast implementation of the iterative correction method and is based on a memory-efficient data format for Hi-C contact maps. In addition, HiC-Pro can use phased genotype data to build allele-specific contact maps. We applied HiC-Pro to different Hi-C datasets, demonstrating its ability to easily process large data in a reasonable time. Source code and documentation are available athttp://github.com/nservant/HiC-Pro .